Transnational Organization: Religious Moderation Among Jamaah Tabligh (JT) in Pekanbaru City - Khotimah; Abd Ghofur; Alpizar; Ridwan Hasbi (Islam Realitas: Journal of Islamic and Social Studies, 2024)
While the Tabligh Jamaat is perceived as phenomenal in its acts of worship (appearing distinct from most other Muslim groups), it demonstrates moderate behavior in societal interactions. In line with other research findings, the Tabligh Jamaat is regarded as a politically neutral organization, which calls for further exploration of its position in implementing the values of religious moderation. Thus, the study of religious moderation becomes a significant area of focus. This paper presents research findings on the extent to which the values of religious moderation are implemented by the Tabligh Jamaat community in Pekanbaru, while also introducing a new orientation in their da'wah (Islamic preaching) as a form of novelty. This study employs a qualitative method with a snowball sampling technique. This method was chosen because snowball sampling facilitates the identification of key informants or leaders within community groups. Starting with one primary informant, the researcher can gain access to other individuals with relevant knowledge or experience.The findings reveal that the development of Tabligh Jamaat's da'wah in Pekanbaru has progressed beyond grassroots efforts to become a movement with clear directions and trends, particularly in educational institutions (pesantren). It was found that the implementation of religious moderation in Pekanbaru is characterized by respect for differences in Islamic schools of thought (madhhab), avoidance of fanaticism, and prioritization of the unity of the ummah (Muslim community). The orientation and methods that have emerged include the adjustment of da'wah methods, a contextual da'wah approach, collective and pragmatic involvement, as well as active and dialogical engagement.